Understanding Customer Value - Identify Customer Value in Existing Features, Products and Systems to Inform Decision-Making - Holmesten, Felix; Thim, Lukas (My University, 2024)
This thesis presents the development and validation of a new framework aimed at addressing the challenges in the field of customer value and product management. Through a comprehensive literature review and interviews with industry professionals multiple key challenges were identified that formed the basis of for the framework. The framework itself focuses on understanding what constitutes value in existing features, products, or systems utilizing hypotheses and metrics to conduct experiments. The experiment results are then used to predict and calculate the expected value of new features. Conducting a validation workshop demonstrated the effectiveness of the framework, guiding the participants to a better understanding of value and successfully mitigating some of the identified challenges. Despite the successes of the framework, it also acknowledges certain limitations and presents opportunities for refinement and future research. Nevertheless, the frameworks accessibility and potential for practical applicability in industry highlights the contributions it brings to the field. The framework presents a practical solution to challenges in the field of customer value and product management, with its potential benefits recognized and validated by industry professionals.
Keywords: Customer Value; Product Management; Framework Development; Modeling of Value; Digitalization; Data-Driven Development; Experiment-Driven Development